Microbiological threats to homeland security. - Yadav, P. (IEEE Engineering in medicine and biology magazine)
The American Type Culture Collection (ATCC) preserves, distributes, and disseminates data on a wide spectrum of microbiological agents. Figure I illustrates the types of information that can be obtained from ATCC's knowledge bases. As research generates more detailed data on microbes that can potentially be used for bioterror, it is becoming obvious that certain types of data must be restricted to legitimate users, just as distribution of these agents is highly regulated.